2020
DOI: 10.1016/j.dental.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an ethanol cross-linker on universal adhesive

Abstract: Objective. To evaluate the effects of N,N'-dicyclohexylcarbodiimide (DCC), an ethanol-based dentin cross-linker, on the immediate and long-term microtensile bond strength (TBS) and nanoleakage expression of a universal adhesive employed in self-etch mode (SE) or etchand-rinse mode (ER). The effect of DCC on the dentinal MMP activity was also investigated by means of in-situ zymography.Methods. Eighty freshly extracted human molars were sectioned to expose mid-coronal dentin surfaces. The teeth were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…An advantage of cross-linkers over MMP inhibitors is that they possess a dual protection role. On one hand, they cross-link and reinforce collagen molecules, and on the other, they inactivate MMPs (Bedran-Russo et al 2008; Bedran-Russo et al 2010; Cova et al 2011; Mazzoni et al 2013; Tjäderhane et al 2013; Bedran-Russo et al 2014; Breschi et al 2018; Comba et al 2020). Specifically, EDC reacts with the carboxyl group on the C-terminus of 1 polypeptide chain, forming an intermediate that reacts with the amino group on the N-terminus of a neighboring polypeptide chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of cross-linkers over MMP inhibitors is that they possess a dual protection role. On one hand, they cross-link and reinforce collagen molecules, and on the other, they inactivate MMPs (Bedran-Russo et al 2008; Bedran-Russo et al 2010; Cova et al 2011; Mazzoni et al 2013; Tjäderhane et al 2013; Bedran-Russo et al 2014; Breschi et al 2018; Comba et al 2020). Specifically, EDC reacts with the carboxyl group on the C-terminus of 1 polypeptide chain, forming an intermediate that reacts with the amino group on the N-terminus of a neighboring polypeptide chain.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable efforts have been invested in developing strategies to minimize HL degradation over time, with recent emphasis on biomodification of tooth tissues (Bedran-Russo et al 2014). Cross-linkers covalently bond collagen molecules, not only increasing the resistance of the resin-sparse, water-rich collagen matrix within the HL against enzymatic degradation, but inactivating dentinal MMPs as well (Bedran-Russo et al 2008; Bedran-Russo et al 2010; Cova et al 2011; Mazzoni et al 2013; Tjäderhane et al 2013; Bedran-Russo et al 2014; Maravic, Breschi, et al 2017; Breschi et al 2018; Comba et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is possible that the MMPs exhibit different functions and levels of activity in primary and permanent dentine, which might have implications in everyday clinical practice. It has been reported that endogenous dentine MMP expression and activation contribute to degradation of the hybrid layer in permanent dentine [ 31 , 32 , 33 , 34 , 35 ]. It is not uncommon to over-etch when using etch-and-rinse adhesives, creating an etching depth that is beyond the depth of infiltration of adhesive resin monomers into the demineralised collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, exogenous MMP inhibitors such as chlorhexidine, galardin, benzalkonium chloride or quaternary ammonium salts contain a functional group that can interact with the Zn 2+ ion in the MMP molecule blocking its activation [1,[24][25][26][27][28]. On the other hand, synthetic and natural cross-linkers such as genipin, carbodiimide (EDC) or grape seed extract form intermolecular and intramolecular collagen cross-links by means of stable covalent bonds, increasing the resin-dentin interface longevity [29][30][31][32]. Furthermore, cross-linkers have also been reported to decrease collagenolytic activity and inactivate MMPs [30,33,34].…”
Section: Discussionmentioning
confidence: 99%